Importance of Video-EEG Monitoring in the Diagnosis of Epilepsy in a Psychiatric Patient. (25th March 2013) - Kirmani, Batool F.
Abstract : Epilepsy is a chronic medical condition which is disabling to both patients and caregivers. The differential diagnosis of epilepsy includes psychogenic nonepileptic spells or "pseudoseizures." Epilepsy is due to abnormal electrical activity in the brain, and pseudoseizure is a form of conversion disorder. The brain waves remain normal in pseudoseizures. The problem arises when a patient with significant psychiatric history presents with seizures. Pseudoseizures become high on the differential diagnosis without extensive work up. This is a case of woman with significant psychiatric issues which resulted in a delay in the diagnosis of epilepsy.